Sistem Pembagian Warisan pada Anak Angkat di Sungguminasa Kecamatan Sombaopu Kabupaten Gowa - Rezky Azhari; Darman Manda (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
The research aims to find out; 1). How Fair is the Distribution of Inheritance of Adopted Children in the Sungguminasa Village, Somba Opu District, Gowa Regency. 2). To find out the Inheritance Sharing System for Adopted Children in Sungguminasa Village, Somba Opu District, Gowa Regency. In this study used a type of qualitative research and written descriptively. Data collection techniques were carried out using observation and documentation methods involving individuals from several informants. The results and conclusions of this study indicate that adopted children can inherit property from their adoptive parents. Because the adoptive parents have considered the adopted child the same as biological children. So that the adoptive parents give their wealth to the adopted child, then the adopted child is obliged to take care of his adoptive parents like biological parents.